Identified Skeletal Collections - Henderson, Charlotte Yvette (Archaeopress, 2018)
Human skeletons are widely studied in archaeological, anthropological and forensic settings to learn about the deceased. This book focusses on identified skeletal collections and discusses how and why collections were amassed and shows the vital role they play in improving methods and interpretations for archaeological and forensic research.